2007
DOI: 10.1007/s00348-007-0412-1
|View full text |Cite
|
Sign up to set email alerts
|

Flowfield measurements in the wake of a robotic lamprey

Abstract: Experiments are reported on the hydrodynamics of a swimming robotic lamprey under conditions of steady swimming and where the thrust exceeds the drag. The motion of the robot was based on the swimming of live lampreys, which is described by an equation similar to that developed for the American eel by Tytell and Lauder (J Exp Biol 207:1825-1841, 2004. For steady swimming, the wake structure closely resembles that of the American eel, where two pairs of same sign vortices are shed each tail beat cycle, giving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 8 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…In the apparatus, the robotic fish is mounted on a servo guide rail system and the towing speed is not preset but determined by the measured force acting on the body of the fish. Some previous studies have investigated hydrodynamics by using robots, but most of the robotic models did not satisfy selfpropelled conditions [4,19]. Encouraged by the potential generality of this simultaneous measurement method based on a force-feedback technique, we believe that unsteady biofluid dynamic experiments can be conducted using the present method, in such areas as the robotic undulatory fin [47,48], pulsed jet propulsion [49], or other biomimetic devices [50].…”
Section: Investigating Fish Biomechanics With Self-propelled Robotsmentioning
confidence: 99%
“…In the apparatus, the robotic fish is mounted on a servo guide rail system and the towing speed is not preset but determined by the measured force acting on the body of the fish. Some previous studies have investigated hydrodynamics by using robots, but most of the robotic models did not satisfy selfpropelled conditions [4,19]. Encouraged by the potential generality of this simultaneous measurement method based on a force-feedback technique, we believe that unsteady biofluid dynamic experiments can be conducted using the present method, in such areas as the robotic undulatory fin [47,48], pulsed jet propulsion [49], or other biomimetic devices [50].…”
Section: Investigating Fish Biomechanics With Self-propelled Robotsmentioning
confidence: 99%
“…[15], Tytell and Lauder [16] and Hultmark et al . [17]). Fish and Lauder [18] have indicated that the wake structure is different between eel-like (anguilliform) fishes and fishes with a narrow tail peduncle region ( e .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the imposed kinematics were quantified using a midline displacement function h(x,t) = a(x) sin(kx − ωt), which describes a traveling wave with spatially dependent wave amplitude a(x) and wave speed c = ω/k, where x is the position along the length of the fish, head to tail, k is the wave number (reciprocal of wavelength), and ω is the oscillation frequency. In the anguilliform case, a(x) was fit to an exponential function matching the data from Tytell and Lauder [21] based on American eels, and the wave number k was set based on the value used for a robotic lamprey [4]. In the carangiform case, the wave amplitude a(x) was expressed as a quadratic fit to the amplitude observations of Videler and Hess [15], with a wavelength based on studies by Videler and Wardle [22].…”
Section: Background On Fish Kinematicsmentioning
confidence: 99%
“…A greater understanding of their movement allows for better appreciation of fish themselves, as well as * Address all correspondence to this author valuable insight to a very efficient form of underwater locomotion. The work in this area can also be applied to the development of modern technology, as today there is a lot of interest in biomimetic robotic fish [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%